2018
DOI: 10.1080/00365513.2018.1488177
|View full text |Cite
|
Sign up to set email alerts
|

D-dimer during pregnancy: establishing trimester-specific reference intervals

Abstract: Pregnancy is associated with an increased risk of venous thromboembolism (VTE). D-dimer is a biomarker used as an exclusion criterion of VTE disease, but its usefulness during pregnancy shows limitations because D-dimer levels physiologically increase through pregnancy. The aim of our study was to follow the changes of D-dimer levels and to establish trimester-specific reference intervals during normal pregnancy. This is a longitudinal prospective study in which the reference population finally included 102 he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(36 citation statements)
references
References 18 publications
3
32
0
1
Order By: Relevance
“…One study reported levels of: 0.11 to 0.40 μg/mL, 0.14 to 0.75 μg/mL, and 0.16 to 1.3 μg/mL in first, second, and third trimester, respectively, 40 while in another study 1.7 μg/mL was reported as the upper limit in the third trimester 35 . Yet another report found a D‐dimer > 0.5 μg/mL in 99% of women during the third trimester 41 . In the recent study by Tang et al, an elevated D‐dimer was one of the predictors of mortality in the non‐pregnant population with COVID‐19, with levels of 2.12 μg/mL (range 0.77–5.27 μg/mL) in COVID‐19 non‐survivors compared to 0.61 μg/mL (range 0.35–1.29 μg/mL) in survivors 30 .…”
Section: Covid‐19 Coagulopathies In Pregnancymentioning
confidence: 89%
“…One study reported levels of: 0.11 to 0.40 μg/mL, 0.14 to 0.75 μg/mL, and 0.16 to 1.3 μg/mL in first, second, and third trimester, respectively, 40 while in another study 1.7 μg/mL was reported as the upper limit in the third trimester 35 . Yet another report found a D‐dimer > 0.5 μg/mL in 99% of women during the third trimester 41 . In the recent study by Tang et al, an elevated D‐dimer was one of the predictors of mortality in the non‐pregnant population with COVID‐19, with levels of 2.12 μg/mL (range 0.77–5.27 μg/mL) in COVID‐19 non‐survivors compared to 0.61 μg/mL (range 0.35–1.29 μg/mL) in survivors 30 .…”
Section: Covid‐19 Coagulopathies In Pregnancymentioning
confidence: 89%
“…In terms of biomarkers, it is known that D-dimer levels, an exclusion criterion for VTE, increase during pregnancy and peak in the third trimester at levels above the conventional cut-off, making them of little use [23]. Several studies have looked at recording D-dimer reference intervals during the three trimesters in healthy pregnancy and suggested pregnancy-associated cut-off levels that may assist clinical decision-making on VTE prophylaxis [23, 24]. Soluble fibrin monomer forms a complex with fibrinogen in the bloodstream early in coagulation, and measuring levels of the complex has also been proposed as a marker to screen for VTE [25].…”
Section: Methodsmentioning
confidence: 99%
“…For patients receiving heparin treatment, the limited range was APPT > 90.00 s. If the patient is undergoing anticoagulation therapy, even though the test result of PT was within the routine limited range rather than within the customized limited range, the report would be stopped for manual autoverification and would not be sent to the HIS. For late pregnancy, the upper limit intervals for PT and APTT were decreased by 10%, and the lower limited range for FBG was increased by 10% [14]. For patients undergoing thrombolytic therapy, the limited range for FBG was defined as 1.20 g/L – 4.00 g/L.…”
Section: Methodsmentioning
confidence: 99%
“…Coagulation assays are essential for assessment of patients requiring acute care [11], patients undergoing anticoagulant therapy [12], thrombolytic therapy [13] and pregnancy [14], as well as monitoring of disseminated intravascular coagulation [15]. Currently, in many laboratories the coagulation assays are still released by manual review, verification and release, and reports about autoverification in coagulation are scarce [16].…”
Section: Introductionmentioning
confidence: 99%